2017
DOI: 10.1123/ssj.2016-0172
|View full text |Cite
|
Sign up to set email alerts
|

Not an “Extraordinary Event”: NFL Games and Militarized Civic Ritual1

Abstract: In this article, which was delivered as the Alan G. Ingham Memorial Lecture to the 37th annual conference of the North American Society for the Sociology of Sport, I extend Ingham’s ideas regarding sport as civic ritual and combine it with my own work on the relationship between sport and the increasing militarization of US cities in the post 9/11 era. I suggest that militarized civic rituals have now become an ever-present feature of urban life and represent a troubling new conflation between military and civ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…Sport and sport media played an important pedagogical role in the hyper-patriotic, racialized backlash following the events of 11 September 2001 in the United States (Silk, 2013). This was especially true for the NFL that branded itself as patriotic and militaristic (King, 2008;Schimmel, 2017). The result was an image of the nation as under attack from both within and without by irrational, dark-skinned "evil doers".…”
Section: Patriotism and Nationalism In Sportsmentioning
confidence: 99%
“…Sport and sport media played an important pedagogical role in the hyper-patriotic, racialized backlash following the events of 11 September 2001 in the United States (Silk, 2013). This was especially true for the NFL that branded itself as patriotic and militaristic (King, 2008;Schimmel, 2017). The result was an image of the nation as under attack from both within and without by irrational, dark-skinned "evil doers".…”
Section: Patriotism and Nationalism In Sportsmentioning
confidence: 99%
“…I do not wish to repeat the authors' argument, Tools of the game. Qualitative digital methodologies for the e-sports research but I found it close to the studies of rituals in regular sports in terms of their politics (Schimmel 2017) and ideologies (Kossakowski et al 2020). Similar avenue is surfacing in e-sports studies (Szablewicz 2016) as well as in analyses of Twitch streaming (Uva 2018).…”
Section: Digital Ethnographymentioning
confidence: 56%
“…American football embodies both definitions of spectacle. As sport theorist Kimberly Schimmel (2017) observes, when millions of people around the United States gather to watch the game with friends and family, we are participating in a civic ritual that, like sacred or mundane rituals, performs the values and belief systems that govern a community. American football illuminates our competitive nature and our willingness to employ violence and aggression to win.…”
Section: Spectacles and Black Powermentioning
confidence: 99%